Effect of different biofertilization strategies on wheat (Triticum turgidum) flour metabolomics - Silvia Sánchez-Méndez; Luciano Orden; Manuel Viuda-Martos; Raquel Lucas González; Francisco Javier Andreu-Rodríguez; Miguel Ángel Mira-Urios; José Antonio Sáez-Tovar; Encarnación Martínez-Sabater; Raúl Moral (Applied Food Research)
The synthesis and accumulation of bioactive compounds in crops is influenced by both environmental and genetic factors, with fertilization being a key environmental determinant. The aim of this study was to evaluate the effects of different fertilization regimes on the metabolomic profile and grain quality of wheat, including starch content and flour colour. The treatments consisted of high phosphorus pellets at sowing (50 kg P ha−¹) and high nitrogen pellets at tillering (150 kg N ha−¹), using three types of fertilizer: (i) organic pellets (OF) derived from agro-food by-products, (ii) organic-mineral pellets (OMF) and (iii) synthetic fertilizers (IN). A control group (no fertilization) and a conventional treatment (standard synthetic NPK) were included for comparison. Metabolomic profiling was conducted using proton nuclear magnetic resonance (¹H-NMR), while the starch content and colour parameters of the flour were also measured. The results revealed that treatments combining organic and mineral fertilizers significantly increased starch content by up to 19% compared to the control and improved flour lightness (L* value). These treatments also enhanced the accumulation of key primary metabolites, including amino acids (such as glutamine and proline) and organic acids (such as malate and citrate), indicating a more favourable nutritional profile. These insights support the development of more sustainable, nutritionally focused wheat production systems.